Children and sport - Olds, T.; Dollman, J.; Ridley, K.; Boshoff, K.; Hartshorne, S.; Kennaugh, S. (2004)
This report addresses five main questions: (a) How and why are young people involved in different kinds of physical activity? (b) Which types of young people are active, and how and why do they get involved in sport? (c) Are there `good news` stories about the benefits of sport, and how young people can successfully combine their involvement in sport with other positive life pursuits, such as success at school? (d) What strategies are necessary to encourage and sustain lifelong involvement in sport and physical activity? (e) What further research is needed to reliably monitor, evaluate and investigate the efficacy of sport and physical activity programs designed for young people?